Diagnóstico de enfermedades producidas por hongos de los tres principales parques del espacio público de la ciudad de Latacunga 2021. - Mármol Calle, Mikaela Jazmín (2021)
Urban parks are green spaces implemented by the human being, their objective is to provide environmental benefits for society, among them they stand out, provide shade, produce oxygen, avoid soil erosion, beautify the city, regulate the climate, that is why that it is seen the need to protect said green spaces from any harmful activity for these green spaces. The purpose of this work was to identify the diseases caused by fungi present in the three main parks of the city of Latacunga (Vicente León Park, Filantropía Park, La Laguna Park) and to form a proposal for the recovery of plant health using an in- situ to identify the type of plant species found in each green space. The identification of diseases caused by fungi was based on a very important component such as the observation of the infected plant material in order to provide useful photographic material in the evaluation and recognition of phytopathogenic microorganisms, for their identification these were carried out in an exhaustive way evaluating the diseases that affect the three main parks and with the help of the incidence percentage we were able to give exact data on the damage caused by fungal diseases Finally, a proposal for the recovery of plant health in the three main parks was proposed, it is focused on monitoring, disease prevention, disease control, creating awareness, environmental culture to citizens regarding the protection of green areas, train the personnel in charge of the parks and reforest the parks with native species according to the ornamental species obtained and adapted to the environmental conditions of the city.